Intelligent sensing, instrumentation and measurements - Mukhopadhyay, Subhas Chandra (Smart sensors, measurement and instrumentation, 2013)
"Intelligent Sensing, Instrumentation and Measurements" addresses issues towards the development of sensor nodes for wireless Sensor Networks. The fundamentals of sensors, interfacing, power supplies, configuration of sensor node, and GUI development are covered. The book will be useful for engineers and researchers in the field ,especially for higher undergraduate and postgraduate students as well as practitioners working on the development of Wireless Sensor Networks or Smart Sensors.